ULTRASONIC DIAGNOSTICS OF THE CONDITION OF SHORT TUBULAR BONES AT LOCAL COLD INJURY IN FINDING THE TACTICS OF THERAPY - Abdullayev, R. Yа.; Grigoryeva, T. G.; Oleynik, G. A.; Yefimenko, S. G. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
For the first time ultrasonic research of the condition of short tubular bones of extremities in patients with local cold injuries (frostbites) was carried out. The appreciable damages of a cortical layer of periosteum, internal diameter of bones even in prereactive period of cryoinjury were revealed. The received results have allowed to define the proper tactics and timeliness of carrying out of conservative and surgical treatment.